Beauty Standard for New Normal: What Indonesian Beauty Advertising Tell Us? - Dana Afriza (Conference Series, 2020)
This paper aims to examine how beauty product brand advertisements adapt to new habits due to the Covid-19 pandemic. A brand list of 295 brands was compiled. The keyword "ad + 2020 + (brand name)" is used for the Google Images search engine. This study found that the majority of beauty advertisements in Indonesia did not respond to the Covid-19 pandemic at all. This research also found that beauty advertisements in Indonesia that responded to the Covid-19 pandemic did so in five ways, namely campaigning to fight the Covid-19 pandemic, providing discounts and free shipping, providing protection for consumers outside the home, campaigning for CSR, and further promoting the products. This research is limited to beauty product brands in Indonesia. Overall, this study provides a new picture of how beauty product advertisements were run in Indonesia during the Covid-19 era.